2006
DOI: 10.1002/ajmg.a.31395
|View full text |Cite
|
Sign up to set email alerts
|

Major feeding difficulties in the first reported case of interstitial 20q11.22‐q12 microdeletion and molecular cytogenetic characterization

Abstract: We report on a 4-year-old female presenting with intrauterine growth retardation, facial dysmorphic features, major feeding difficulties with severe diarrhea and vomiting, mental retardation with abnormal behavior and hypertonia. Feeding difficulties were the most invalidating features with absent oral intake requiring persistent enteral feeding. Standard cytogenetic studies were normal, but high-resolution chromosome analyses revealed a small de novo interstitial deletion of the long arm of chromosome 20, 46,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 8 publications
3
29
1
1
Order By: Relevance
“…GHRH haploinsufficiency may lead to isolated growth hormone deficiency (GHD) and justify the marked prenatal and postnatal growth retardation found in our patient and in about half of the published cases [Callier et al, 2006;Iqbal and Al-Owain, 2007;Hiraki et al, 2011;Gervasini et al, 2013;Posmyk et al, 2014;Jedraszak et al, 2015]. This hypothesis seems to be supported by the reduced IGF1 levels in our patient.…”
Section: )supporting
confidence: 75%
See 3 more Smart Citations
“…GHRH haploinsufficiency may lead to isolated growth hormone deficiency (GHD) and justify the marked prenatal and postnatal growth retardation found in our patient and in about half of the published cases [Callier et al, 2006;Iqbal and Al-Owain, 2007;Hiraki et al, 2011;Gervasini et al, 2013;Posmyk et al, 2014;Jedraszak et al, 2015]. This hypothesis seems to be supported by the reduced IGF1 levels in our patient.…”
Section: )supporting
confidence: 75%
“…Mutations and deletions of SAMHD1 have been associated with systemic lupus erythematosus, and recently homozygous mutations in SAMHD1 were found in 8.3% of Jedraszak et al, 2015Callier et al, 2006Iqbal et al, 2007Hiraki et al, 2011Gervasini et al, 2013Posmyk et al, 2014 Total reported patients Our case (DECIPHER…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…To our knowledge, a total of 12 patients have been reported in the literature [Petersen et al, 1987;Shabtai et al, 1993;Aldred et al, 2002;Genevieve et al, 2005;Callier et al, 2006;Borozdin et al, 2007;Iqbal and Al-Owain, 2007]. Among them, only two cases showed the proximal q deletion (20q11-q12), not extending to q13 [Callier et al, 2006;Iqbal and Al-Owain, 2007]. One patient had a 6.6-Mb deletion at 20q11.21-q11.23 [Callier et al, 2006], and the other [Iqbal and Al-Owain, 2007] showed a 6.8-Mb deletion at 20q11.2-q12.…”
Section: Introductionmentioning
confidence: 99%